The micro and macro of a large and sudden devaluation - Andrea Ariu; Giulia Rivolta (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2025)
This paper quantifies the micro- and macro-level consequences of the sudden appreciation of the Swiss franc in 2015, one of the sharpest and most persistent currency movements in recent decades. Using detailed firm-level data on French imports and exports, we show that the Swiss franc appreciation led to a rise in exports, driven mainly by the entry of new firms and new products, while imports increased only briefly due to a spike in prices among continuing firm-product pairs. These dynamics mirror a textbook J-curve adjustment and reveal the firm-level mechanisms underlying this aggregate response. On the macro side, we trace how the shock propagated through supply chains, capturing both direct and indirect exposures through input-output linkages. This network-based perspective uncovers a small but negative overall impact on French GDP, driven by the stronger hit to importers, more reliant on non-euro currencies and more central within domestic production networks, who acted as key conduits transmitting the negative side of the shock across the economy.
Keywords: F14; F31; F44; 330; Exchange rate shocks; international trade; production network